Clover Leaf Drying Efficiency Using a Drying Machine with a Solar Cell - Muhandhis, Isnaini; Ni'matul Ichsan, Muchammad Ragil; Fernando, Ferdianus; Reyhan Rizqi, Muhammad; Riyanto, Ong Andre Wahyu; Ritonga, Alven Safik (Fakultas Teknik-Universitas Wijaya Putra, 2023)
Kendung Village is known as